EFISIENSI RUMAH SAKIT JIWA PEMERINTAH DI PROVINSI JAWA TENGAH DAN DIY SEBELUM DAN SESUDAH JKN DENGAN MENGGUNAKAN TWO-STAGE DATA ENVELOPMENT ANALYSIS (DEA) - Rina Indrayanti; Lutfan Lazuardi; Mubasysyir Hasanbasri (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: During a national health insurance implementation, efficiency improvement becomes an important issue as a result of the change of a payment method from free for service to fixed pricing mechanism of INA CBG’s by containing cost and improving quality. Inefficiency occurs when a psychiatric hospital uses an excessive input resource to produce a given level output. Objective: This study aimed to measure the level of efficiency of government psychiatric hospitals in the provinces of Central Java and Yogyakarta before and after the implementation of JKN. Methods: A descriptive quantitative study was conducted using two-stage data envelopment analysis (DEA). The first stage was to measure hospital efficiency. Second stage used paired samples t-test to analyze different mean of BOR, LOS, BTO, TOI and cost efficiency score. This study used secondary data from financial report, human resources report, hospital patient visit report of 5 psychiatric hospitals in central java and DIY province, period 2010 until 2014. Results: Efficiency measurement using DEA CRS inputoriented model obtained the mean of cost efficiency score was 0,896. Mean of efficiency score decreased during a transition period of national health insurance implementation from 0,947 in 2013 became 0,866 in 2014. Soedjarwadi hospital was the only one of a psychiatric hospital that achieved cost efficiency in 2014. Paired samples t test analysis showed that there was no difference of mean of BOR, LOS, BTO, TOI and score cost efficiency before and after efficiency improvement in 2013 from 2010. There was no difference of mean of BOR, LOS, BTO and score efficiency before and after implementation of national health insurance. The only one variable had difference of mean before and after implementation of national health insurance was TOI. Conclusion: Most psychiatric hospital in this study are still inefficient. National health insurance has not been able to improve efficiency in the early implementation period. Decreasing of efficiency score happened because of the decreasing of hospital output.